Coats-like retinitis pigmentosa: Reports of three cases - Kan, Emrah; Yilmaz, Turgut; Aydemir, Orhan; Guler, Mete; Kurt, Julide (Dove Medical Press Ltd, 2007)
Purpose: Describing the ophthalmic findings of an exudative vasculopathy called as Coats-like retinitis pigmentosa on three patients. The etiology of the Coats-like retinitis pigmentosa is obscure. The principal theories have been discussed in this article. Methods: Three observational case series have been discussed. Complete ophthalmic examinations and color fundus photos, visual field, and fluorescein angiography have been performed. Results: We have identified 3 patients who have some typical clinical features of Coats-like retinitis pigmentosa; peripheral serous retinal detachment, telangiectasia, prominent lipid deposition, pigmentary changes in peripheral retina, and loss of vision. None of the three patients had positive family history. All of the patients have had symptoms of nyctalopia, decreased central vision, and two of them have had constriction of visual field. All of the patients have had cataracts and two of them underwent cataract surgery. Fundus examination and fluorescein angiography of patients revealed typical retinitis pigmentosa with Coats-type changes in bilateral inferiotemporal quadrants. Conclusion: A better understanding of clinical features and genetic etiology of Coats-type retinitis pigmentosa will aid diagnosis and development of new therapies. If sufficient conditions arise, genetic factors that influence the expression of CRB1 mutations in Coats-like retinitis pigmentosa should be detected.
Keywords: Coats-like retinitis pigmentosa; exudative retinal detachment